2020
DOI: 10.4269/ajtmh.19-0566
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Pediatric Meningitis in West Africa Using Molecular Methods in the Era of Conjugate Vaccines against Pneumococcus, Meningococcus, and Haemophilus influenzae Type b

Abstract: Despite the implementation of effective conjugate vaccines against the three main bacterial pathogens that cause meningitis, Streptococcus pneumoniae, Haemophilus influenzae type b (Hib), and Neisseria meningitidis serogroup A, the burden of meningitis in West Africa remains high. The relative importance of other bacterial, viral, and parasitic pathogens in central nervous system infections is poorly characterized. Cerebrospinal fluid (CSF) specimens were collected from children younger than 5 years with suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…More recently, a commercial TaqMan Array card has been developed that can detect multiple meningitis-associated pathogens [47] . This assay was tested in CSF samples originating from West Africa and results indicated that diverse infectious aetiological agents were present.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a commercial TaqMan Array card has been developed that can detect multiple meningitis-associated pathogens [47] . This assay was tested in CSF samples originating from West Africa and results indicated that diverse infectious aetiological agents were present.…”
Section: Introductionmentioning
confidence: 99%
“…Although data collected through all these surveillance programs were used to support the implementation of vaccines and monitor vaccine impact, there remain large gaps in the understanding of meningitis across most African countries, particularly beyond early childhood and the 3 main bacterial pathogens (pneumococcus, meningococcus and H. influenzae ) [ 30 ].…”
Section: Current Meningitis Surveillance Systems and Their Limitationsmentioning
confidence: 99%
“…More recent data show that the global incidence of meningitis increased from 2.5 million cases in 1990 to 2.82 million cases in 2016, with the highest rates found in sub-Saharan African countries, also known as the meningitis belt [ 4 ]. Kwambana-Adams et al published the prevalence of bacterial, viral and parasitic infection in children younger than 5 years of age in West Africa following the rollout of conjugate vaccines against pneumococcus (PVC), meningococcus (MenAfriVac) and Haemophilus influenzae [ 5 ]. Escherichia coli (4.8%), followed by S. pneumoniae (3.5%) and Plasmodium (3.5%), were the most prevalent etiologies of meningitis in this age group.…”
Section: Introductionmentioning
confidence: 99%